Effective utilization of 3D representation in mobile device for pedestrian navigation aid - Alhaji Liman, Mukhtar; Abubakar, Adamu (Centre for Promoting Ideas, USA, 2013)
Digital (Three-Dimensional) 3D map representation of a city or any location in mobile device provides information about environment to which its represents, sometimes even more details than reality. These ease the problems of reading information added by the paper map which not everyone can read. Unfortunately, in some cases using 3D representation for pedestrian navigation aid in mobile devices cannot be generalized in terms of its effectiveness. This is because in some certain situation where a user expects its benefits most, it does harm rather than good. This paper investigates the factors that determine effective utilization of 3D representation in mobile device for Pedestrian Navigation Aid. This study is conducted via qualitative interviews in order to unveil situational feelings of users with regard to the effective utilization of 3D representation in mobile devices for the purpose of solving the problems of finding unknown locations easily. Issues concerning functional specification, application content quality, and the interaction quality are the major aspect of the problems identified by the respondent of this study. Thus, findings reveal that, stability, ease of use, condition of use, accuracy, and feedbacks exert crucial influences on the use of 3D representation in mobile device for pedestrian navigation aid. We also find out that the use of 3D representation creates more visual understanding of an environment by enhancing the degree of 3D users’ perception.